The Photoshop Elements 8 pocket guide - Gyncild, Brie (Peachpit Press, 2010)
Adobe Photoshop Elements 8 marries sophisticated capabilities with a user-friendly interface. That's why it's a good choice for just about anyone who wants to enhance and improve their photos. This pocket guide offers a quick introduction to Elements 8 and acts as a handy reference. Both Mac and Windows versions are covered along with new features such as People Recognition, Auto-Analyzer, any-size photo recomposition, one-step color and lighting adjustments, multiple computer photo library synchronization, and more. Other sections include common editing tasks, quick fixes, managing images in Organizer (Windows) and Bridge (Mac), and saving and sharing photos.